Psychometric properties of the Persian version of Self-Injurious Thoughts and Behaviors Questionnaire-Nonsuicidal (SITBQ-NS) in an Iranian outpatient sample - Sara Sobhani; Banafsheh Gharraee; Mojgan Salavati; Komeil Zahedi Tajrishi; Hojjatollah Farahani; Alessandra D'Agostino (Acta Psychologica)
Nonsuicidal self-injury (NSSI) is a clinically significant behavior often associated with several psychiatric disorders, underscoring the importance of accurately assessing both NSSI thoughts and behaviors. The Self-Injurious Thoughts and Behaviors Questionnaire-Nonsuicidal (SITBQ-NS) is a self-report instrument designed to assess the full range of NSSI thoughts and behaviors. However, the psychometric properties of the SITBQ-NS have not been adequately investigated, particularly in Eastern cultures. To address this gap, the present study examined the psychometric properties of the Persian version of the SITBQ-NS using data from 350 outpatients (age range: 18–60 years, M = 27.65, SD = 6.61; 20 % male) recruited from two psychiatric hospitals and two university counseling and psychological services centers in Tehran, Iran. Confirmatory factor analysis (CFA) supported the originally proposed two-factor model, showing excellent internal consistency and the expected associations with relevant external correlates. Furthermore, receiver operating characteristic (ROC) analysis revealed excellent sensitivity and specificity for the SITBQ-NS subscale scores, demonstrating its effectiveness in identifying NSSI. Overall, the results suggest that the Persian version of the SITBQ-NS has a robust factor structure and is a reliable, valid tool for assessing NSSI thoughts and behaviors in clinical and research settings in Iran.